Pengaruh Penggunaan Aditif Pakan Terhadap Kualitas Kalsium Tulang Broiler - S.A.Wahidin; M.N. Hidayat (Jurnal Ilmu dan Industri Peternakan, 2023)
This study aims to determine the effect of antibiotics (Zinc bacitracin) and multi-strain probiotics (Lactobacillus casei, Saccharomyces cerevisiae and Rhodopseudomonas palustris) on broiler bone quality. The method used was a Completely Randomized Design (CRD) with 4 treatments and 4 replications. The parameters measured were the increase in length and percentage of calcium content of the tibia and femur bones. The method for analyzing broiler calcium content uses the Atomic Absortion Spectrophotometer (AAS) method. Research treatments on broilers, namely: Basal ration (control) (P0), Basal ration + Multi Strain Probiotics (1-35 days), 1.5 ml/day (P1), Basal ration + Antibiotics (1-35 days), 0.1 g/day (P2) and Basal Ration + 0.1 g/day Antibiotics (1-21 days) + Multi strain probiotics (22-35 days), 1.5 ml/day (P3). The results showed that treatment (antibiotics and probiotics) on the length of the tibia and femur in broilers obtained P1 (7.3 cm), P2 (7.1 cm), P3 (7.1 cm) and P0 (7.0 cm) did not significant effect (P>0.05). Meanwhile, the percentage of bone calcium in the tibia and femur has a significant effect (P<0.05) with percentages P0(10.2%), P1 (14.4%), P2 (12.4%) to P3 (10.6%) so that it can It was concluded that administration of the antibiotic Zinc Bacitracin and multi-strain probiotics (Lactobacillus casei, Saccharomyces cerevisiae and Rhodopseudomonas palustris) in drinking water had a significant effect on the calcium content of the tibia and femur bones. Meanwhile, administration of the antibiotic Zinc Bacitracin and multi-strain probiotics (Lactobacillus casei, Saccharomyces cerevisiae and Rhodopseudomonas palustris) in drinking water did not significantly affect the length of the tibia and femur in broilers.